IMPROVING STUDENTS’ PARTICIPATION IN LEARNING READING COMPREHENSION OF NARRATIVE TEXTS THROUGH CONSTRUCTIVE READING MODEL (CRM) - Maenawati, Ida (Universitas Negeri Semarang, 2013)
This article is a report of an action research project conducted in reading class for Eleventh Year Students of State Senior High School 7 Cirebon in the Academic Year of 2012/2013. The objectives of this study are to describe: (1) the problems faced by the students in learning reading comprehension (2) how Constructive Reading Model is implemented (3) whether Constructive Reading Model improve students’ participation in learning reading comprehension . The result from the questionnaires and observation sheet showed that(1) the students did not actively participate in the process of teaching learning, (2) by using Constructive Reading Model students’ participation from pre-cycle to cycle 1 increased , from cycle 1 to cycle 2 increased, and (3) students’ score of reading comprehension from pre-cycle to cycle 1 increased 15.65 points, from cycle 1 to cycle 2 increased 11.59 points. So the study concluded that the implementation of Constructive Reading Model (1) could solve the problems faced by the students in learning reading comprehension (2) could improve students’ participation in the process of teaching learning and(3) could develop students’ reading comprehension mastery of the Eleventh Year Students of State Senior High School 7 Cirebon.